Prace legislacyjne nad ustawą o stosunku państwa do Muzułmańskiego Związku Religijnego w Rzeczypospolitej Polskiej - Baszak, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
After regaining its independence the Second Polish Republic inherited various legal systems from the partitioning powers. They differed with regard to both legal institutions and legal constructs. This state of affairs hindered the integration of the state and caused a lot of problems in socio-economic relations. This was reflected also in the law dealing with religions. The reborn Polish state had to define the legal status of churches and religious associations, among others.The author of the article presents the work associated with the regulation of the legal status of the Muslim Religious Association. The Muslims, who were, with few exceptions, Polish Tatars, were a small minority in the Second Polish Republic. Nevertheless, they managed, following more than a decade of consultations with the government, to have the Act adopted, in accordance with Article 115 of the March Constitution. The Constitution was also the basis of the issuance of an ordinance concerning the recognition of the internal statutes of the association.
Keywords: prawo wyznaniowe II RP; stowarzyszenia mniejszości wyznaniowych II RP; muzułmanie; Tatarzy; Islam; Muzułmański Związek Religijny; ustawa o stosunkach Państwa z Muzułmańskim Związkiem Religijnym